Effectiveness and safety of selected traditional Chinese medicine injections in patients with combined diabetes mellitus and coronary heart disease: A systematic review and network meta-analysis of randomized clinical trials - Hailiang Shen; Ping Zhou; Luyao Shen; Chenhao Ju; Haixia Du; Xianguo Qu (Frontiers Media S.A., 2023)
Background: In view of the high morbidity and mortality of Diabetes mellitus-Coronary heart disease (DM-CHD) in diabetics, the combination therapy of traditional Chinese medicine injections (TCMIs) and conventional therapy (CT) is receiving extensive attention. Therefore, the effectiveness and security of conventional therapy with traditional Chinese medicine injections in the therapy of diabetes mellitus-coronary heart disease were compared by systematical review and network meta-analysis.Methods: According to the preset inclusion criteria and exclusion criteria, we searched seven electronic literature databases from their inception to JAN 5,2022, to obtain the relevant RCT literature on the therapy of diabetes mellitus-coronary heart disease with traditional Chinese medicine injections. Two researchers independently reviewed the papers, two other researchers worked in extracting data and quality assessment of the included literature. The primary outcomes were total effective rate. The secondary outcomes included electrocardiogram (EGG)effective rate, the effective rate of angina pectoris, fasting blood glucose (FBG), 2-h postprandial blood glucose (PBG), hemoglobinA1c (HbA1c), total cholesterol (TC) and triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), frequency of angina pectoris, and duration of angina pectoris. We adopted stata16.0 software for the systematic review and network meta-analysis.Results: A total of 53 trials involved 4,619 patients and one of the following 16 traditional Chinese medicine injections: Danhong, Danshen, Gualoupi, Gegen, Chuanxiongqin, Danshenchuanxiongqin, Shenmai, Shenqi, Xixin, Xuesaitong, Shuxuetong, Guanxinning, Kudiezi, Ciwujia, Xingding, Shuxuening. The meta-analysis revealed that Chuanxiongqin injection was superior to all other therapies in improving the total effective rate, [vs. conventional therapy odds ratio (OR): 14.52, 95% confidence interval (CI): 4.13-51.02], vs. Xuesaitong injection (odds ratio: 7.61, confidence interval: 1.25-46.40), and vs. Danshenchuanxiongqin injection (odds ratio: 3.98, confidence interval: 1.03-15.28)]. Xixin injection + conventional therapy was superior to conventional therapy only for electrocardiogram effective rate (odds ratio: 5.44, confidence interval: 1.55-19.18). Shenmai injection + conventional therapy was superior to conventional therapy in effective rate of angina (odds ratio: 11.05, confidence interval: 2.76-44.28). There was not different significantly in the comparisons of frequency of angina pectoris and duration of angina pectoris, we considered that this may be due to the lack of sufficient data. As most of the included RCTs did not monitor Adverse Events, the safety of those traditional Chinese medicine injections remains to be further explored.Conclusion: Basing on our study, traditional Chinese medicine injections combined with conventional therapy takes important role in the treatment of diabetes mellitus-coronary heart disease, and its curative effect is better than conventional therapy. Nevertheless, properly designed RCTs are required to validate our conclusions in the future.Systematic Review Registration: [https://inplasy.com/inplasy-2021-12-0125/], identifier [INPLASY2021120125].